NBA game progression of extreme score shifts and comeback analysis: A team resilience perspective - Goldschmied, N.; Mauldin, K.; Thompson, B.; Raphaeli, M. (Asian Journal of Sport and Exercise Psychology, 2024)
We focus on the construct of team resiliency in analyzing data from NBA games hitting a 20-point deficit in the first half during the 1997/8 to 2021/2 seasons to determine the frequency of comebacks and the ability to mount a game winning resurgence temporally. First, we found that 20-point deficits and comebacks were more likely in recent seasons. Yet overcoming the odds and mounting a successful comeback were still achieved in only 7 % of the 3,942 qualified games. Moreover, games, that reached the 20-point deficit much earlier, were more likely to be overturned (i.e., comebacks) as they seemed not to reflect true differences in abilities between the teams in contention but a random tilt towards one team and then a correcting shift towards its opponent (i.e., regression to the mean). Also, games that hit the 20-point mark and were then tied did not show a winning momentum towards the resurging team. These trends should put emphasis on team resilience strategies at the participatory level of players and coaches through practice simulations and communication as well as through empirical research to identify specific team correlates with these extreme point shifts.